MERS-CoV infection in South Korea and strategies for possible future outbreak: narrative review - Chulwoo Park (Inishmore Laser Scientific Publishing Ltd, 2019)
Although there were some positive viewpoints from international press and academia that the Republic of Korea (hereafter South Korea) successfully controlled the Middle East Respiratory Syndrome (MERS) outbreak in 2015, the domestic point of view towards the MERS response in South Korea was critical. As people in the world's 11^th^ largest economy, South Koreans criticized the failure of hospitals' initial response to the MERS index case and the lack of a proper control strategy for secondary and tertiary cases. To contain the MERS outbreak, South Korea implemented mainly three MERS control and intervention strategies: quarantine and isolation system, temporary closure of schools and cancelation of public events, and share of correct knowledge of MERS from trustworthy authorities, such as central and local governments and non-governmental organizations (NGOs). The traveler tracking system, the health care delivery system, and the Infectious Disease Prevention Act should be strengthened or amended. The establishment of bioethics and adherence to the World Health Organization (WHO)'s guidelines are also recommended to prevent possible future outbreak.